The molecular investigations on the subgenus Artemisia Less. of the genus Artemisia L. (Asteraceae) in Turkey - Yilmaz Sancar, P.; Tukur, U.; Civelek, S.; Kursat, M. (Instituto Internacional de Ecologia, 2023)
The genus Artemisia L. of the family Asteraceae is systematically very complex. The aim of this study was to evaluate taxonomic positions of taxa of the subgenus Artemisia belonging to the genus Artemisia in Turkey using some molecular techniques. In this molecular study, 44 individuals belong to 14 species of the subgenus Artemisia were examined. Analyses were performed on the combined dataset using maximum parsimony, maximum likelihood and Bayesian inference and Molecular parameters obtained from co-evaluations of sequences of the psbA-trnH, ITS and ETS regions of examined individuals were used in the phylogenetic tree drawing. According to the results of this study, two molecular groups have been formed based on the DNA sequence similarity of the species, but there are no obvious morphological characters corresponding to two molecular groups. There is no also agreement between the two molecular groups and the two morphological groups formed according to the hairiness condition of the receptacle of species. Due to the lack of molecular significance of their receptacles with or without hair, dividing of the subgenus Artemisia species into new subgenera or sections was not considered appropriate. Likewise, it has been found that with or without hair on the corolla lobes of the central hermaphrodite disc flowers have no molecular significance. It was found that there were no gene flow and hybridization between the 14 species of the subgenus Artemisia and these 14 species were found completed their speciation. This study is important as it is the first molecular based study relating with belong to subgenus Artemisia species growing naturally in Turkey. In addition, new haplotypes related to the populations of Turkey belonging to the subgenus Artemisia taxa were reported by us for the first time and added to the GenBank database. © 2023, Instituto Internacional de Ecologia. All rights reserved.
Investigações moleculares sobre o subgênero Artemisia Less. do gênero Artemisia L. (Asteraceae) na Turquia
Keywords: Artemisia; ETS; ITS; Phylogeny; PsbA-trnH; Turkey